Corticosteroid treatment regulates mucosal remodeling in chronic rhinosinusitis with nasal polyps. (13th January 2015) - de Borja Callejas, Francisco; Martínez‐Antón, Asunción; Picado, César; Alobid, Isam; Pujols, Laura; Valero, Antonio; Roca‐Ferrer, Jordi; Mullol, Joaquim
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To investigate the effect of oral plus intranasal corticosteroid (CS) treatment on nasal polyp (NP) mucosa remodeling from patients with severe chronic rhinosinusitis with nasal polyps (CRSwNP). Study Design Case series, retrospective study. Methods Patients (n = 18) with severe CRSwNP were treated with oral prednisone for 2 weeks and intranasal budesonide for 12 weeks. NP biopsies were obtained from patients biopsies before (w0) and after 2 weeks (w2) and 12 weeks (w12) of CS treatment. Matrix metalloprotease 1 (MMP‐1), MMP‐2, MMP‐7, MMP‐9, and tissue inhibitor of metalloprotease type 1 (TIMP‐1) expression was evaluated by immunohistochemistry in cell and tissue structures. Epithelial damage, eosinophil infiltration, and collagen content were also examined in NP tissues before and after CS treatment. Results Compared to w0: 1) oral plus intranasal CS significantly (P < .01) increased presence of submucosal glands at w2, decreased epithelial cell hyperplasia at w12, and decreased tissue eosinophilia at w2 and w12; 2) CS treatment significantly (P < .05) increased immunoreactivity for MMP‐1 and MMP‐2 in the epithelium at w2, but decreased immunoreactivity for MMP‐9 in the epithelium at w2 and w12; 3) at w12, CS significantly (P < .05) reduced MMP‐9 immunoreactive positivity and intensity in the extracellular matrix, while increasing total collagen amount in the extracellular matrix; and 4) CS treatment significantly (P < .01) reduced the number of eosinophils and their MMP and TIMP‐1 immunoreactive expression. Conclusions CS treatment modulates NP mucosa remodeling, particularly by promoting epithelial repair, regulating tissue remodeling markers, increasing total collagen content, and reducing tissue eosinophil infiltration. Level of Evidence 4 Laryngoscope, 125:E158–E167, 2015